FDI and trade: complements and substitutes - Pontes, José Pedro (2010)
This paper presents a non-monotonic relationship between foreign direct investment and trade based on the idea that, although FDI eliminates trade costs on the final good, the investing firm has to bear increased trade costs on an intermediate good.